VALVULAR BRONCHIAL BLOCKING IN TREATMENT OF RELAPSING SPONTANEOUS PHEUMOTHORAX IN THE PATIENT WITH PARASEPTAL PULMONARY EMPHYSEMA - O. V. Lovacheva; I. Yu. Shumskaya; D. R. Faizullin; E. A. Shergina; I. V. Sivokozov (Туберкулез и болезни лёгких)
Spontaneous pneumothorax was treated by placing two endobronchial valves during rigid bronchoscopy under anesthesia in a patient with severe end-stage chronic obstructive pulmonary disease (an emphysematous phenotype) and overall paraseptal emphysema in the presence of grade III respiratory failure, with complicated spontaneous pneumothorax recurring manifold even after surgical treatment for spontaneous pneumothorax. This gave rise to the expansion of the lung that had collapsed within 18 months, to healing of bronchopleural fistula, and to return to normal life.The duration of a follow-up was 1 year with the valves being present in the bronchi and another year after their removal; there was no recurrence of spontaneous pneumothorax. Examination of respiratory function established significant positive changes (forced expiratory volume, vital capacity, and forced vital capacity after one year, then after removal of endobronchial valves). There were more significant positive changes in blood gas composition: normalization of blood oxygen saturation was achieved.